Bibliometric Analysis of Research Trends in Digital Literacy within Indonesian Education: Development, Challenges, and Opportunities - Aulia, Febrina; Tasrif, Elfi (FKIP Universitas Lampung, 2025)
Bibliometric Analysis of Research Trends in Digital Literacy within Indonesian Education: Development, Challenges, and Opportunities. Objective: The advancement of technology and the increasing reliance on internet-based communication demand digital literacy as an essential skill for technology users. The education sector plays a crucial role in building understanding, implementation, and reinforcement of digital literacy skills. Methods: This study conducts a bibliometric analysis of research trends in digital literacy within Indonesian education using articles indexed in the Sinta database. We found 548 articles and analyze it based on criteria. Finally, 431 articles match the criteria for this study. The search was not time-restricted, allowing the study to identify the earliest research on digital literacy in Indonesia. Findings: The analysis results indicate that research in this field began to be published in 2017 and has seen significant growth up to 2024. The majority of publications are found in journals accredited by Sinta 5, Sinta 3, and Sinta 4, with qualitative research being the most dominant methodology. Additionally, geographical distribution shows that Java Island contributes the highest number of publications. This study covers various educational levels, from early childhood to higher education, with varying contributions at each level. Conclusion: Research on digital literacy in Indonesian education has largely focused on pedagogical approaches, educational technology, and its effects on teachers and students. However, there is ample opportunity for further investigation, particularly in exploring digital literacy within specialized fields, its impact on students' academic and non-academic competencies, and its role in equipping students to be responsible and ethical members of the digital society. Furthermore, future research should extend its geographical coverage beyond Java to provide a more inclusive perspective on the development of digital literacy across diverse regions in Indonesia. Keywords: bibliometric analysis, digital literacy, education, learning, Indonesia.